Development and Promotion of the Agro -Tourism Park in Bangun Harja Village Through Social Media - Lestariningsih, Nanik; Syahputra, M. Adzi Pratama; Tinus, Tinus; Rezeki, Ely Raswati; Yanti, Rahmi; Ardiansyah, Ardiansyah; Kharisma, Kharisma; Nuratih, Siti Dila; Syairazi, Syairazi; Amalia, Risky; Sumantri, Lisa Solihatun (Sasambo: Jurnal Abdimas (Journal of Community Service), 2024)
Bangun Harja Village in East Seruyan Hilir District, Seruyan Regency, Central Kalimantan Province, possesses significant natural potential for development into a tourism destination, particularly as an agrotourism park. Despite its substantial potential, the Bangun Harja Agrotourism Park has not attracted substantial attention from tourists due to inadequate infrastructure, limited human resources, lack of innovation and creativity among managers, and absence of promotion through social media. This community service program aims to increase the popularity and number of visits to the Bangun Harja Agrotourism Park by utilizing social media platforms as the main promotional tool. The program involves students from IAIN Palangka Raya, village officials, and community leaders, and employs the ABCD (Asset-Based Community Development) method to leverage the village’s assets effectively. The key activities include creating and promoting attractive spots within the park, enhancing infrastructure, and conducting social media marketing campaigns. The expected outcomes include increased social media followers, interactions, tourist visits, and local economic benefits. This initiative aims to create a sustainable and thriving agrotourism destination that benefits the local community both economically and socially